Run for Science (R4S): the history of a successful project of precision and laboratory medicine in sport and exercise - Lippi, Giuseppe; Schena, Federico (Journal of Laboratory and Precision Medicine, 2017)
Since ancient times sports has drawn the attention of scientists from a large number of disciplines, including social sciences, physiology, medicine and rehabilitation. Although it is now unquestionable that regular performance of physical exercise is associated with a lower risk of developing many human diseases such as cancer, cardiovascular disorders, diabetes, rheumatic diseases, sarcopenia and frailty, some issues remain to be addressed. These typically include the amount of exercise needed to improve health and fitness without overcoming the putative health befits, along with the insufficient recognition of biological pathways that can be modulated by active lifestyle. The still incomplete knowledge of these aspects is contributing to the growth of several scientific initiatives, specifically aimed to study changes and individual adaptations underlying regular sport practice. The bases, context and early achievements of one of such initiatives, called “Run for Science”, will be summarized in this article. In particular, the various editions of this event have allowed to make new discoveries and tangible advancements in human biology and personalized laboratory medicine, including the observation that cardiac troponins transitorily increase in blood after endurance exercise, that running performance is influenced by two previously unappreciated laboratory parameters (i.e., serum alpha-amylase and mean platelet volume) and that the DNA may undergo a transitory oxidative damage during exercise. More recently, the information gathered from the Run for Science helped discovering important aspects linking physical exercise with the lower risk of cancer, cardiovascular disease and asthmatic reactions. Additional analyses are underway, and specific focus will be placed on sports epigenetics, with the aim to define how recreational sport interplays with gene expression and modifies the individual response to exercise.